SCN5A Genetic Polymorphisms Associated With Increased Defibrillator Shocks in Brugada Syndrome. Issue 6 (5th June 2017) - Makarawate, Pattarapong; Chaosuwannakit, Narumol; Vannaprasaht, Suda; Sahasthas, Dujdao; Koo, Seok Hwee; Lee, Edmund Jon Deoon; Tassaneeyakul, Wichittra; Barajas‐Martinez, Hector; Hu, Dan; Sawanyawisuth, Kittisak
Abstract : Background: Brugada syndrome (BrS) is an inherited primary arrhythmia disorder leading to sudden cardiac arrest. SCN5A, encoding the α‐subunit of the cardiac sodium channel (Nav1.5), is the most common pathogenic gene of BrS. An implantable cardioverter defibrillator (ICD) is the standard treatment for secondary prevention. This study aimed to evaluate association of the SCN5A variant with this cardiac conduction disturbance and appropriate ICD shock therapy in Thai symptomatic BrS patients with ICD implants. Methods and Results: Symptomatic BrS patients diagnosed at university hospital were enrolled from 2008 to 2011. The primary outcome of the study was an appropriate ICD shock defined as having non‐pacing‐associated ICD shock after the occurrence of ventricular tachycardia or ventricular fibrillation. Associations between SCN5A polymorphisms, cardiac conduction disturbance, and potential confounding factors associated with appropriate ICD shock therapy were analyzed. All 40 symptomatic BrS patients (median age, 43 years) with ICD implantations were followed for 24 months. There were 16 patients (40%) who had the appropriate ICD shock therapy after ICD treatment. An independent factor associated with appropriate ICD shock therapy was SCN5A‐ R1193Q with an adjusted hazard ratio of 10.550 (95% CI, 1.631–68.232). Conclusions: SCN5A‐ R1193Q is associated with cardiac conduction disturbances. It may be a genetic marker associated with ventricular arrhythmia leading to appropriate ICD shock therapy in symptomatic BrS patients with ICD treatment. Because of the small sample size of study population and the appropriate ICD shock outcome, further large studies are needed to confirm the results of this study.